Freedom of Expression of Judges in Bosnia and Herzegovina - Milinković, Igor M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Freedom of expression is a fundamental human right protected by the major international human rights instruments and national constitutions. The right to freedom of expression is treated as one of the key elements of a democratic society and it can be considered essential to human dignity. However, this right is not absolute and it can, if certain preconditions are met, be subjected to limitations, as indicated by the provisions of the European Convention on Human Rights, as well as the case law of the European Court of Human Rights. Judges also enjoy the right to freedom of expression. Although the participation of judges in debates on matters of public interest is considered very important, especially when it comes to the regulation of the status of judiciary, the nature of the judicial function dictates restrictions on the freedom of expression of judicial office holders in order to protect public confidence in the judicial branch of government and its reputation. Public expression of personal views may raise dilemmas regarding the impartiality of a judge. The paper will draw attention to the importance of protecting the freedom of expression of judges, but also to the issue of necessity and legitimacy of its restrictions. Legal provisions regulating the right to freedom of expression of judges in Bosnia and Herzegovina will be examined, as well as examples from the practice of disciplinary bodies relating to the exercise of the aforementioned right. Legislative solutions adopted in Bosnia and Herzegovina will be compared with provisions adopted in other countries and subjected to critical evaluation.
Keywords: freedom of expression, human rights instruments, judges, restrictions, impartiality, social networks, judicial ethics